Fat jets for a light higgs boson - Plehn, Tilman; Salam, Gavin; Spannowsky, Michael (Physical review letters, 2010)
At the LHC associated top quark and Higgs boson production with a Higgs boson decay to bottom quarks has long been a heavily disputed search channel. Recently, it has been found not to be viable. We show how it can be observed by tagging massive Higgs bosons and top jets. For this purpose we construct boosted top and Higgs taggers for standard-model processes in a complex QCD environment.
Gesehen am 04.05.2023